A New Venue of TNF Targeting - Steeland, Sophie (Int J Mol Sci, 2018)
The first Food and Drug Administration-(FDA)-approved drugs were small, chemically-manufactured and highly active molecules with possible off-target effects, followed by protein-based medicines such as antibodies. Conventional antibodies bind a specific protein and are becoming increasingly important in the therapeutic landscape. A very prominent class of biologicals are the anti-tumor necrosis factor (TNF) drugs that are applied in several inflammatory diseases that are characterized by dysregulated TNF levels. Marketing of TNF inhibitors revolutionized the treatment of diseases such as Crohn’s disease. However, these inhibitors also have undesired effects, some of them directly associated with the inherent nature of this drug class, whereas others are linked with their mechanism of action, being pan-TNF inhibition. The effects of TNF can diverge at the level of TNF format or receptor, and we discuss the consequences of this in sepsis, autoimmunity and neurodegeneration. Recently, researchers tried to design drugs with reduced side effects. These include molecules with more specificity targeting one specific TNF format or receptor, or that neutralize TNF in specific cells. Alternatively, TNF-directed biologicals without the typical antibody structure are manufactured. Here, we review the complications related to the use of conventional TNF inhibitors, together with the anti-TNF alternatives and the benefits of selective approaches in different diseases.